2015
DOI: 10.1002/eji.201444999
|View full text |Cite
|
Sign up to set email alerts
|

Development of thymic Foxp3+ regulatory T cells: TGF‐β matters

Abstract: CD4+ regulatory T cells expressing the transcription factor Foxp3 can be generated in the thymus (tTreg cells), but the cellular and molecular pathways driving their development remain incompletely understood. Transforming growth factor-beta (TGF-β) is essential for the generation of Foxp3+ Treg cells converted from peripheral naive CD4+ T cells (pTreg cells), yet a role for TGF-β in tTreg-cell development was initially refuted. Nevertheless, recent studies have unmasked a requirement for TGF-β in the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 54 publications
8
78
0
Order By: Relevance
“…However, the potential involvement of TGF-β in mediating the dynamic phenotypic alterations of infarct macrophage subpopulations remains unknown. TGF-β also serves as a central mediator in T lymphocyte differentiation and activation, critically regulating phenotype and function of all subpopulations (69)(70)(71). Although activated subsets of T lymphocytes have been implicated in repair and remodeling of the infarcted heart (30,32,72), the relative role of TGF-β signaling in their recruitment and activation has not been investigated.…”
Section: Tgf-βmentioning
confidence: 99%
“…However, the potential involvement of TGF-β in mediating the dynamic phenotypic alterations of infarct macrophage subpopulations remains unknown. TGF-β also serves as a central mediator in T lymphocyte differentiation and activation, critically regulating phenotype and function of all subpopulations (69)(70)(71). Although activated subsets of T lymphocytes have been implicated in repair and remodeling of the infarcted heart (30,32,72), the relative role of TGF-β signaling in their recruitment and activation has not been investigated.…”
Section: Tgf-βmentioning
confidence: 99%
“…These molecules mediate immune suppression via different pathways and a downregulation in all 3 molecules could suggest a severe reduction in Treg function. It was shown that TGF‐β was required for Foxp3 expression during thymic Treg development and TGF‐β promotes Foxp3 expression in CD4 + CD25 − T conv cells . The lack of TGF‐β secretion possibly restricted further development of Treg cells and resulted in reductions in Treg frequency in delayed healing patients.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated measures 2-way ANOVA followed by Sidak's multiple comparisons test. *P < .05 expression during thymic Treg development and TGFβ promotes Foxp3 expression in CD4 + CD25 − T conv cells 21. The lack of TGFβ secretion possibly restricted further development of Treg cells and resulted in reductions in Treg frequency in delayed healing patients.…”
mentioning
confidence: 95%
“…The macrophage and fibroblast derived TGF-β also shapes the T cell response as TGF-β promotes the development of regulatory T cells which have been found in prostate cancer and correlates with worse survival. [31] The immunosuppressive microenvironment once established reciprocally supports the expansion of the reactive stroma through sustained production of growth factors and chemokines from the existing inflammatory cells that continually attract inflammatory cells. This cycle produces a microenvironment that supports cell growth in the guise of tissue repair and ultimately allows for the formation and progression of cancer.…”
Section: Tumor-stroma Microenvironment In Prostate Cancermentioning
confidence: 99%